Can Patients Practice Strenuous Sports After Uncemented Ceramic-on-Ceramic Total Hip Arthroplasty?. Issue 4 (4th April 2018) - Bonnin, Michel P.; Rollier, Jean-Charles; Chatelet, Jean-Christophe; Ait-Si-Selmi, Tarik; Chouteau, Julien; Jacquot, Laurent; Hannink, Gerjon; Saffarini, Mo; Fessy, Michel-Henri
Background: Patients are often concerned about returning to sports after total hip arthroplasty (THA). Purpose: To (1) evaluate sports participation and motivation rates in a large cohort of patients who underwent uncemented THA with ceramic-on-ceramic bearings and (2) determine whether patients' participation was associated with their motivation for each sport, preoperative demographics, or patient-reported outcomes. Study Design: Case-control study; Level of evidence, 3. Methods: We surveyed 1310 patients (aged <75 years) who underwent uncemented ceramic-on-ceramic THA and collected levels of motivation and participation for 22 different sports as well as patient-reported outcome measure scores. A total of 1042 patients (1206 hips) returned questionnaires; the mean age at index surgery was 60.6 ± 8.8 years. Results: At least 51% of patients participated regularly or frequently in at least 1 light sport, 73% in at least 1 moderate sport, and 20% in at least 1 strenuous sport. Sports participation was strongly correlated with motivation ( r = 0.97, P < .001) but not with level of discomfort ( r = 0.22, P = .292). Participation in strenuous sports was significantly associated with age, body mass index, and sex. There were significant differences among patients who practiced various categories of sports as determined using the Oxford Hip Score ( P = .008), but not with regard to the Forgotten Joint Score ( P = .054). Conclusion: Only 20% of patients practiced strenuous sports regularly or frequently after THA, regardless of pain or discomfort. Participation in sports after THA is strongly correlated with motivation but not with level of discomfort. Longer term studies with a greater focus on complications and survival are necessary to determine whether high-impact sports compromise patient safety or implant longevity.